Natalia Goncharova’s Rayonism in Coordinates of Abstract Art - Furman, Olga V. (Actual Problems of Theory and History of Art, 2014)
Although studies of both Russian and foreign researchers have covered much ground on the art of Natalia Goncharova, there are still many gaps especially in the fi eld of her non-fi gurative painting.  The focus of this article lies in the early and late Goncharova’s works which display her contact with the abstract art. Mostly it concerns her rayonistic painting made in the 1910’s, as well as in the 1950s. Late works done in the non-fi gurative style still have not got a place on the artistic scene of the post-war abstract painting. This topic sets up direct questions on Goncharova’s art. Does the artist’s appeal to the abstract art possess a regular or sporadic character? What was the context of her creative work? Whether it is right to relate some of her works with the genuine abstact art or not? Whether the artist left the area of the figurative painting or did she always swing between the figurative and non-fi gurative art? These questions call upon wide problems of the specifi cs of the Russian abstract art as a whole and of the Russian emigrant’s art in particular. Th e analysis of Goncharova’s creative work in this aspect may provide with a possibility to understand the nature of her artistic method and probably to reconstruct Goncharova’s attitude to the abstract painting, her view on the possibilities and limits of this art
Keywords: Painting; non-fi gurative art; abstract art; rayonism; Natalia Goncharova; Michail Larionov; Russian emigrants’ art